Synthesis of Naphthylamines and Anthrylamines via η3-Benzylpalladium Intermediates - Zhang, Sheng; Bao, Ming (Synlett, 2012)
The alkylative dearomatization of benzyl chlorides via η3-benzylpalladium intermediates has been developed for carbocycle synthesis. This article highlights the current progress in the area of η3-benzylpalladium chemistry. A new method has been established for naphthylamine and anthrylamine synthesis.
Keywords: palladium; catalysis; amination; arylamine; synthesis